Commercial diplomacy and multistakeholder diplomacy (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Intention of the paper is to emphasize the fact that the commercial diplomacy today becomes less statecentred and more multistakeholder in its substance. The context is aimed to the analysis and discussion if commercial diplomacy has the attributes of multistakeholder diplomacy. The summary of main actors involved in commercial diplomacy is presented and types of structures used by governments performing commercial diplomacy are described. Additionally, the role of state and non-state actors in commercial diplomacy is discussed together with differences between state-centred and multistakeholder diplomacy. Finally, the attributes of a commercial diplomacy from the perspective of the multistakeholder diplomacy are highlighted.